Immersive Learning Through AR/VR: Enhancing Cognitive Understanding and Retention in Virtual Classrooms. (Journal of Digital Learning Futures p-ISSN 3117-6054 and e-ISSN 3117-6062, 2025)
The rapid evolution of immersive technologies such as Augmented Reality (AR) and Virtual Reality (VR) has introduced transformative possibilities in education. Unlike conventional classroom-based learning, immersive learning replicates real-world experiences through visualization, simulation, and interaction. This research evaluates the impact of AR/VR on cognitive comprehension, memory retention, and student engagement in virtual classrooms. Through a mixed-method experimental design involving 260 students across three academic institutions, learners were divided into two groups: one taught using traditional methods and the other via AR/VR tools. Quantitative and qualitative data revealed that immersive learning environments improve conceptual clarity by 47%, increase long-term retention by 62%, and enhance attention span by 55% compared to traditional classrooms. The findings emphasize that AR/VR learning supports active participation, boosts curiosity-driven exploration, and reduces cognitive fatigue by transforming abstract concepts into real-life simulated experiences. The study concludes that integrating immersive technologies in education enhances cognitive learning outcomes and prepares students for future digital ecosystems.